ANALISIS DAMPAK PANJANG WAKTU SEKOLAH TERHADAP PEMBENTUKAN NILAI-NILAI PENDIDIKAN ISLAM DI TADIKA AL-FIKH ORCHARD, MALAYSIA - Dian Wijaya Kusuma; Muhammad Qorib (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the effect of extended school duration on the formation of Islamic educational values at the Tadika level in Al-Fikh Orchard School, Malaysia. A descriptive qualitative approach was applied through observation, semi-structured interviews, and documentation involving the principal, teachers, and parents. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that full-day schooling supports the internalization of aqidah, worship, moral conduct, and social values through consistent habituation embedded in daily activities. Teacher role modeling and a religious school culture strengthen the process. Properly managed school duration contributes to effective Islamic character formation among participants.